History Of African Accounting Thoughts And Development: Evidences From Igbo Land - Onuoha, Luke N.; Enyi, Patrick E. (Archives of Business Research, 2019)
The aim of this paper was to present the history of accounting thought in Africa with particular focus on Igbo land. The study is carried out via desk research. Secondary sources from journals, textbooks, internet sources and oral accounts have been adopted. The study reveals that Igbo people had a rich history of accounting thought which has remained partially documented. In some ways, accounting development experience of the Igbos was similar to the pre-history period experience of Mesopotamia, Egypt and other early civilizations as there were unique methods in the use of notches on sticks, vertical and horizontal marks on the wall, use of counters made of pebbles, grains and palm kernel stored in calabashes and wooden boxes as measurements of wealth. The 1494 double entry system published by Luca Pacioli, an Italian monk and mathematician, which brought sweeping changes in the method of recording business transactions across Europe and America, similarly affected the development of accounting in Nigeria. Also the formation of accounting bodies in Europe and America between 1854 and 1897 influenced similar developments in Nigeria which culminated in 1960 to the formation of the Association of Accountants in Nigeria and subsequently the charter of the Institute of Chartered Accountants of Nigeria (ICAN) by the Parliament in 1965. The formation of the International Accounting Standards Board (IASB) in 1979 added the dimension of internationality and comparability to the reporting quality in Nigeria. This paper will be of critical significance to accounting history researchers and students.